COGNITIVE-ENHANCING PROPERTIES OF MORINDA LUCIDA (RUBIACEAE) AND PELTOPHORUM PTEROCARPUM (FABACEAE) IN SCOPOLAMINE-INDUCED AMNESIC MICE - Taiwo O, Elufioye; Halimah A., Hameed (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: Cognitive disorders associated with aging have been successfully managed by African traditionalmedical practitioners using various plants. This study evaluated the cognitive enhancing potentials of Morinda lucida(L) Rubiaceae and Peltophorum pterocarpum (DC) ex. K Heyne in scopolamine induced amnesic animals.Materials and Methods: The anti-amnesic activity of the ethyl acetate extracts of Morinda lucida and Peltophorumpterocarpum at doses of 4 mg/kg, 6 mg/kg and 8 mg/kg were assessed in scopolamine induced amnesic mice usingMorris water maze test model. Effect of the extracts on the histology of the hippocampus was also evaluated.Results: The ethyl acetate extract of Morinda lucida and Peltophorum pterocarpum ameliorated scopolamine inducedmemory deficit in the animals under study. There was no effect of the extract on the histology of the hippocampus.However, there was an increase in the density of cells in the hippocampus of treated group as compared to theuntreated.Conclusion: Morinda lucida and Peltophorum pterocarpum showed considerable enhancement of cognition inscopolamine induced amnesic mice.